Distinct IgG recognition patterns during progression of subclinical and clinical infection with lymphadenopathy associated virus/human T lymphotropic virus. Issue 6515 (25th January 1986) - Lange, J M; Coutinho, R A; Krone, W J; Verdonck, L F; Danner, S A; van der Noordaa, J; Goudsmit, J
Abstract : Longitudinal IgG recognition patterns of viral proteins were studied in 15 men who had seroconverted for lymphadenopathy associated virus/human T lymphotropic virus (LAV/HTLV-III). Antibodies to the major viral core protein p24, which is a cleavage product of the gag gene encoded precursor protein pr55, appeared first. These were soon followed by antibodies to pr55 and more gradually by antibodies to the other gag gene encoded cleavage product p18, the env gene encoded transmembrane glycoprotein gp41, the env gene encoded glycoproteins gp65 and gp110, and the putative pol gene product p33. In 13 subjects who remained healthy the reactivity to the different proteins increased or stabilised with time, while in two men who developed acquired immune deficiency syndrome (AIDS) the reactivity, most noticeably to gag encoded proteins, diminished before or at the onset of symptoms.